Elementary School Teacher Education Lecturers' Perception of Science Technology Engineering Arts and Mathematics (STEAM) in Elementary Science Learning - Trivena; Hakpantria; Yeusi Rombe (MIMBAR PGSD Undiksha, 2025)
STEAM based learning is viewed as a strategic approach in elementary education for fostering critical thinking, creativity, and problem-solving skills. However, its successful implementation is strongly influenced by educators’ perceptions and readiness as key instructional agents. This study aims to analyze PGSD lecturers’ perceptions regarding their knowledge, attitudes, and readiness to integrate STEAM into science learning, including constraints related to limited supporting facilities. A descriptive qualitative approach was employed, involving six permanent lecturers as research participants. Data were collected through in-depth interviews guided by an instrument that highlights aspects of STEAM-related knowledge, attitudes, and implementation readiness, and subsequently analyzed thematically. The findings indicate that the lecturers possess a solid understanding of STEAM concepts, its relevance to the Industrial Revolution 5.0, and its contribution to curriculum development. In terms of attitudes, all lecturers demonstrated positive views and conceptual readiness to implement STEAM as a means of strengthening 21st century skills. However, implementation in practice remains limited due to inadequate supporting facilities and insufficient institutional support. This study concludes that lecturers’ perceptions of STEAM fall within a positive category, although its implementation requires stronger reinforcement. The implications highlight the need for institutions to provide adequate learning facilities, expand professional development opportunities for lecturers, and design internal policies that systematically promote the integration of STEAM so that science learning can be carried out more effectively, innovatively, and sustainably.